INTEGRATION OF INTERDISCIPLINARY RELATIONS IN TRAINING IS THE BASIS OF THE PROCESS (Journal of Pharmaceutical Negative Results, 2023)
For the sake of development of modern sciences, there has been a tendency in education to make use of integration processes between sciences. Interdisciplinary integration and coordination is one of the characteristic features of the learning process which is an interconnected and fully integrated discipline. Creating interdisciplinary integration, focusing on strengthening student knowledge and skills, teaching Computer Science in relationship with other disciplines, such as mathematics, physics, biology and others, is an area of interest. This method of teaching requires instructors to be fluent not only in their own discipline, but also in other disciplines.The method of interdisciplinary relationship can be widely used in the teaching of Computer Science in relation to the course of Physics, and this opportunity is one of the actual problems. For the purpose of fulfilling this task, curriculums of both disciplines have been researched and analyzed. Certain topics from the Physics course are reminded students as a refresh to reinforce the knowledge once again, and then on the basis of this knowledge, Computer Science topics are taught, which helps consciously master the new knowledge and increase cognitive activity of students. In this study, to solve physics problems we have employed the programming language C ++, which is a universal language with a wide range of capabilities.This article justifies actuality of the issue, gives background on the existing work, and presents goals and tasks of this research, as well as methodological basics, scientific novelty, and theoretical and practical importance of this work. Experiments have been conducted with the key points emerging from the context have been presented in the conclusion section. In conclusion, one of the ways to improve the teaching of Computer Science is the use of interdisciplinary relationships in the educational process. These interdisciplinary relationships play an important role for students in acquisition of scientific, theoretical and practical knowledge and skills. These relationships can be a prerequisite for a comprehensive approach to education.